FROM THE HISTORY OF MUSIC EDUCATION AND PEDAGOGICAL SYSTEM ACTIVITY IN UZBEKISTAN IN THE 1950s-1970s (Academia Science Repository, 2023)
The article is devoted to such issues as the essence of the system of musical pedagogy in Uzbekistan in the middle of the twentieth century, the organization of music classes in schools, the content of educational and methodological documents, musical education and aesthetic education. of the younger generation and the development of a system for training music teachers.